ENHANCED PRODUCTION LEVEL OF QUININE IN CELL SUSPENSION CULTURE OF Cinchona ledgeriana Moens BY PACLOBUTRAZOL - Diah Ratnadewi (BIOTROPIA, 2013)
Quinine is one of the major alkaloids in Cinchona spp., and it is used both as a medication and as a drink additive. The plant produces most of its alkaloids in the bark after 6–8 years of age.Repeated harvests can be performed until the plant dies, but only after every 3–5 years. We tested an improved method for culturing cell suspensions of Cinchona ledgerianato investigate the possibility of increasing production of quinine. The clone QRC 315 was treated with either a growth retardant (abscisic acid or paclobutrazol) or precursor feeding of L-tryptophan. To generate stress, we applied mannitol at 5.3 g/L combined with sucrose at a lower concentration (20 g/L),and we used sucrose at 30 g/L as the control. Paclobutrazol (7 mg/L) significantly suppressed cell growth and produced the highest level of quinine (11%) after 7 weeks of culture. L-tryptophan also reduced cell growth, but without any positive effect in the production of quinoline. The highest amount of quinine per culture flask, however, resulted in cells treated with 3 mg/L abscisic acid.